Degradation of ornithine decarboxylase: exposure of the C-terminal target by a polyamine-inducible inhibitory protein. - Li, X (1993)
Polyamine-mediated degradation of vertebrate ornithine decarboxylase (ODC) is associated with the production of antizyme, a reversible tightly binding protein inhibitor of ODC activity. The interaction of antizyme with a binding element near the N terminus of ODC is essential but not sufficient for regulation of the enzyme by polyamines (X. Li and P. Coffino, Mol. Cell. Biol. 12:3556-2562, 1992). We now show that a second element present at the C terminus is required for the degradation process. Antizyme caused a conformational change in ODC, which made the C terminus of ODC more accessible. Blocking the C terminus with antibody prevented degradation. Tethering the C terminus by creating a circularly permuted, enzymatically active form of ODC prevented antizyme-mediated degradation. These data elucidate a form of feedback regulation whereby excess polyamines induce destruction of ODC, the enzyme that initiates their biosynthesis.